2018
DOI: 10.1080/23802359.2018.1502635
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequences of two Boehmeria species (Urticaceae)

Abstract: Boehmeria is an important genus; however, no plastid genome has been reported to date. Here we report the complete chloroplast genomes for two Boehmeria species. The chloroplast genomes of Boehmeria umbrosa and Boehmeria spicata were found to be 170920 bp and 170958 in length, respectively, and the GC contents were 35.5 and 35.3%, respectively. The sequences of each species contained 112 unique genes, including 30 tRNA, 4 rRNA, and 78 protein-coding genes. This is the first report of cp genomes for Boehmeria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Previous studies showed that the genera of Boehmeria and Debregeasia species were each closely clustered into one group (Wu et al. 2018 ; Fu and Zhang 2021 ), which was consistent with our study results of phylogenetic analysis. However, the phylogenetic analysis of Laportea genus has not been reportedyet, its the first time to make phylogenetic analysis for L. bulbifera species.…”
supporting
confidence: 93%
“…Previous studies showed that the genera of Boehmeria and Debregeasia species were each closely clustered into one group (Wu et al. 2018 ; Fu and Zhang 2021 ), which was consistent with our study results of phylogenetic analysis. However, the phylogenetic analysis of Laportea genus has not been reportedyet, its the first time to make phylogenetic analysis for L. bulbifera species.…”
supporting
confidence: 93%
“…Plastome provides sufficient information to resolve the phylogenetic relationships at generic and infrageneric level. Despite several plastid genomes of species in Urticaceae have been reported (Wu et al 2017;Wu et al 2018;Fu et al 2019;Wang et al 2020), none of them belong to Procris.…”
mentioning
confidence: 99%
“…Chloroplast genome provides additional information to resolve the phylogenetic relationships at generic and infrageneric level. Within Urticaceae, only three chloroplast genomes of two Boehmeria and one Cecropia species have been published (Wu et al 2017;Wu, Du et al 2018) to date; these genera belong to the tribes other than Elatostemateae.…”
mentioning
confidence: 99%